2018
DOI: 10.1038/s41598-018-32208-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of incorporation of granule-lyophilised platelet-rich fibrin into polyvinyl alcohol hydrogel on wound healing

Abstract: Dressings are commonly used to treat skin wounds. In this study, we aimed to develop a new scaffold composed of a polyvinyl alcohol (PVA) hydrogel containing granule-lyophilised platelet-rich fibrin (G-L-PRF) as a dressing. G-L-PRF was prepared by freeze-drying and was then incorporated into PVA hydrogel by freezing-thawing. Notably, the mechanical strength and degradation rate of the scaffold were found to be related to G-L-PRF concentrations, reaching 6.451 × 10−2 MPa and 17–22%, respectively, at a concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…In the past, topical wounds are typically treated and managed with traditional dressings. 35 Xu et al fabricated a novel granule-lyophilised platelet-rich fibrin-loaded polyvinyl alcohol hydrogel scaffolds as an ideal wound dressing material for skin tissue regeneration. Notably, the characterisation studies revealed the excellent morphology, biocompatibility, biodegradability (17-22%), and mechanical strength (6.451×10−2MPa) of this granulelyophilised platelet-rich fibrin loaded polyvinyl alcohol hydrogel scaffolds.…”
Section: Fibrinmentioning
confidence: 99%
“…In the past, topical wounds are typically treated and managed with traditional dressings. 35 Xu et al fabricated a novel granule-lyophilised platelet-rich fibrin-loaded polyvinyl alcohol hydrogel scaffolds as an ideal wound dressing material for skin tissue regeneration. Notably, the characterisation studies revealed the excellent morphology, biocompatibility, biodegradability (17-22%), and mechanical strength (6.451×10−2MPa) of this granulelyophilised platelet-rich fibrin loaded polyvinyl alcohol hydrogel scaffolds.…”
Section: Fibrinmentioning
confidence: 99%
“…Interestingly, in contrast to the nontreated group, this study revealed a significant (p < 0.01) fivefold increase in blood vessel density in the LPC group. Recently, Xu et al [15] suggested that the vascularization process was accelerated in their skin wound study in mice after using a scaffold composed of polyvinyl alcohol (PVA) hydrogel and LPCs as a dressing within 9 days post-surgery. Hence, they believe the neo-angiogenesis could provide oxygen and nutrient to the surgical site, thus promoting protein synthesis.…”
Section: Craniofacial Wound Healingmentioning
confidence: 99%
“…Finally, due to the requirement for the need for their use within a short time-frame, as they cannot be easily stored or transported, their application is not well suited for emergency care medicine [14]. These issues restrict the use of PCs for broader therapeutic applications [15].…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] To overcome these shortcomings, implantation of platelet-rich fibrin (PRF) has paid greater attention nowadays, to enhance healing. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%